Escaping from ancient Rome! Applications and challenges for designing smart cities. Issue 1 (January 2014) - Heo, Taewook; Kim, Kwangsoo; Kim, Hyunhak; Lee, Changwon; Ryu, Jae Hong; Leem, Youn Taik; Jun, Jong Arm; Pyo, Chulsik; Yoo, Seung‐Mok; Ko, JeongGil; Dohler, Mischa; Ratti, Carlo; et al.
ABSTRACT From ancient Europe, the renaissance and industrialisation eras, to the modern times, urban planning paradigms have evolved in many ways, advancing the environments where people live in. Nevertheless, the recent development of wireless and wired communication network technologies and low‐power miniature sensors for various application domains provide us with another chance of revolutionising cities by making them smarter. Smart cities, propelled by a city‐scale infrastructure, where information provided from different application systems integrate together, will initiate the development of new applications that can benefit our everyday lives. This article presents an overview of representative applications that consist a smart city with their respective challenges and application requirements. Furthermore, we share our experiences obtained from designing and deploying examples of such smart systems in multiple application domains and summarise the remaining challenges for making the vision of designing smart cities a reality. Copyright © 2014 John Wiley & Sons, Ltd.